Effects of different lasers on organic/inorganic ratio of radicular dentin. Issue 3 (April 2016) - Lopes, F.; Roperto, R.; Akkus, A.; Akkus, O.; Souza-Gabriel, A.; Sousa-Neto, M.
Abstract The aim of this study was to evaluate the chemical stability of endodontic-treated root dentin after different laser irradiations through Raman spectroscopy. Fifty maxillary canines were selected and prepared with K3 system. Roots were randomly distributed into five groups (n  = 10) according to the surface treatment: GI (water), GII (NaOCl + EDTA), GIII (NaOCl + EDTA + 980 nm Diode laser), GIV (NaOCl + EDTA+ 1064 nm Nd: YAG laser) and GV (NaOCl + EDTA+ 2780 nm Er, Cr: YSGG laser). Lasers were applied for 20 s. Samples were bisected, and the organic and inorganic content of dentin was analyzed by Raman spectroscopy. Data were submitted to ANOVA and Tukey tests (p  < 0.05). None of the surface treatments alter the inorganic content (cts) (p  = 0.183). Roots irradiated with Er, Cr: YSGG laser had a reduced collagen content (GV-290.7 ± 41.7) compared with the water-treated roots (GI-328.3 ± 63.5) and those treated with NaOCl + EDTA (GII-333.9 ± 55.8). Roots irradiated with Er, Cr: YSGG laser also showed a higher inorganic/organic ratio (GV-9.5 ± 1.1) than roots treated with water (GI-7.7 ± 1.5), NaOCl + EDTA (GII-8.0 ± 1.4) and diode laser (GIII-8.2 ± 1.6). Both organic and inorganic contents increased from cervical to apical thirds in all groups. None of the surface treatments were able to promote changes in the inorganic content of the root dentin; treatment with NaOCl + EDTA combined with Er, Cr: YSGG altered collagen.